Ayurvedic Approach Towards The Treatment For Mycobacterium Tuberculosis - Hyma, P; Veni , Marri.Ruthika Ratna; Mamidipalli , Apurva; Harini , Lingam (International Research Journal of Ayurveda & Yoga, 2021)
The Ayurvedic system of medicine is the oldest Indian system of medicine and is being practiced in few places around the globe. Ayurveda is the traditional Hindu system of medicine that is purely based in curing the individuals from any kind of disease or disorder by maintaining a balance of the body systems with the help of diet, herbal treatment and yoga breathing. Tuberculosis is a disease that primarily effects the lungs and rarely the other parts of the body. Tuberculosis effects the lungs by blocking the airways and making it difficult to breathe. There are many ayurvedic remedies or treatments that help cure the Tuberculosis disease. The onset of the disease from the period of the infection to the cure or death of the individual is about three years. In the view of Ayurveda, Tuberculosis is known as Rajyakshma. Tuberculosis is generally caused due to the loss of immunity, loss in tissue and many more. It is primarily caused by the bacterium, Mycobacterium Tuberculosis. In Ayurveda, there are certain procedures or therapies to be followed to completely cure the Tuberculosis. The procedures involve emesis, Oleation, purification, etc. The Ayurvedic procedures work by eliminating the toxins from the body and balancing the Doshas of the body. In this article we are going to discuss about the Tuberculosis in brief, it’s Pathophysiology, the allopathic remedies or treatment involved and the Ayurvedic treatment, procedures and different herbs used in the ayurvedic treatment.